Semport: a personalized semantic portal. - Sah, M; Hall, W; Gibbins, N; Roure, D (ACM, 2007)
This paper presents an ontology-based semantic portal, SEMPort, which aims to support both content providers and the users of the portal during providing information, browsing and searching. The content is enriched with context-based semantic hyperlinks and personalized views. Distributed content editing/provision is supplied for the maintenance of the contents in real-time. As a case study, SEMPort is tested on the school's Course Modules Web Page (CMWP) and evaluated using this domain.